Development of Value Added Anaemic Soup Powder and Its Beneficial Effect - Ankita; Mishra, Sunita (Asian Journal of Science and Applied Technology, 2018)
Anaemia is condition characterized as a low level of haemoglobin in the blood, as evidenced by a reduced quality of red blood cell which decreases oxygen-carrying capacity to tissues. The whole idea of development of Value Added Anaemic Soup Powder rich in iron .Which include Beetroot, Tomato, Carrot, Pea, Ragi Flour, Corn Flour. This product is in rich fiber content, iron, protein, carbohydrate etc. This processed product is beneficial for anaemic patient. 15gm Value Added Anaemic Soup Powder and mix it one bowl boiled water.Take this regularly meal.The main objective of the study is to know the Value Added Anaemic Soup Powder and its beneficial effect.